The behavioral relevance of multisensory neural response interactions - Sperdin, Holger F.; Cappe, Céline; Murray, Micah M. (Frontiers in Neuroscience, 2010)
Sensory information can interact to impact perception and behavior. Foods are appreciated according to their appearance, smell, taste, and texture. Athletes and dancers combine visual, auditory, and somatosensory information to coordinate their movements. Under laboratory settings, detection and discrimination are likewise facilitated by multisensory signals. Research over the past several decades has shown both that the requisite anatomy exists to support interactions between sensory systems in regions canonically designated as exclusively unisensory in their function and more recently that neural response interactions occur within these same regions, including even primary cortices and thalamic nuclei, at early post-stimulus latencies. Here, we review evidence concerning direct links between early, low-level neural response interactions and behavioral measures of multisensory integration.